Peran Komitmen Dalam Menghindari Ihtikar Sembako di Pasar Krembangan Surabaya (Studi Pada Mahasiswa Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Universitas Airlangga) - Mirzha Ayunirraga; Moh. Qudsi Fauzi (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
Dealing transaction in sharia Islam is main purpose to every muslims as muammalah (worship) behavior acted. The merchants commintment is basic point to establish ethics and muslim merchants behavior according to Rasulullah SAW taught to avoid prohibited dealing transactions in sharia Islam. One of the forbidden form in Islamic dealing transaction is ihtikar (accumulated foodsupplies). The main point of these research to knows understanding behavior commitment of muslim merchants in Krembangan traditional market Surabaya to avoid the forbidden one in Islam, which is Ihtikar (accumulated foodsupplies). The research method used qualitative within descriptive study case. The informant determine by purposive sampling. Data samples are collected by semi–structured interview. The results of this research shown that was in generally, muslim merchants has understood commitment behavior acts within sincerity intention, hard work, truth, unity, and khiar (determination)principles to avoid ihtikar.